1981
DOI: 10.2307/3429283
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Induced Leukemia in Humans

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Unfortunately animal bioassays are, in general, a poor model for myelotoxic effects in humans. A recent survey of a wide range of human leukemogens showed that all produced only solid tumors in mice or rats, including lymphomas, but no nonlymphatic leukemias [20]. This review noted that the lack of suitable animal models necessitates more reliance "on single case reports or clusters of cases in which chemical exposures are associated with acute leukemia."…”
Section: Carcinogenicity Of Chlordane/heptachlormentioning
confidence: 99%
“…Unfortunately animal bioassays are, in general, a poor model for myelotoxic effects in humans. A recent survey of a wide range of human leukemogens showed that all produced only solid tumors in mice or rats, including lymphomas, but no nonlymphatic leukemias [20]. This review noted that the lack of suitable animal models necessitates more reliance "on single case reports or clusters of cases in which chemical exposures are associated with acute leukemia."…”
Section: Carcinogenicity Of Chlordane/heptachlormentioning
confidence: 99%
“…For example, multiple immune derangements occurring as a result of chemical exposure include altered cell‐mediated immunity 28 and hormone production 29,30 . Functional abnormalities in the immune system following toxin exposure include neoplastic disorders such as leukemias which are seen to be significantly elevated among farmers exposed to agricultural chemicals 31–33 and among individuals occupationally exposed to petroleum products 31 . These factors taken in context with the potent capacity of BuChE as a detoxifying agent may account for the inverse relationship between levels of activated T cells and activity of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study of childhood leukemia (59) that, in addition to EMF, occupational exposures to pesticides and insecticides were associated with increased rates of acute leukemia. Exposures to chemicals that have been linked with leukemia risk in occupational situations are also found in other settings (66). Risks from household exposure to some of these chemicals have not been studied.…”
Section: Urban/rural Factorsmentioning
confidence: 98%